2008
DOI: 10.1159/000156482
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Serum HBV DNA and No Change Apportioned by the Same Hepatic Parenchyma Cell Volume from Hepatic Fibrosis Stage 1 to Stage 4 during the Natural History of Chronic Hepatitis B

Abstract: During the initial phase of chronic hepatitis B virus (HBV) infection, serum HBV DNA levels are high. Contrarily, fibrosis, cirrhosis and hepatocellular carcinoma have been found in patients with lower serum HBV DNA levels. The aim of this study is to clarify HBV DNA level dynamics of serum apportioned by the same hepatic parenchyma cell volume (HPCV) in hepatic fibrosis stages 1–4 during the natural history of chronic hepatitis B. Serum HBV DNA levels were evaluated by real-time polymerase chain reaction. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…As hepatic fibrosis progresses, the liver parenchyma cell volume decreases and can cause changes in viral loads. Previous studies have reported that the severity of hepatic injury is not consistent with the serum HCV load in HCV-infected patients (12,13). Therefore, it can be hypothesized that hepatic injury is associated with the HCV load in the parenchyma cells of HCV-infected patients.…”
Section: Introductionmentioning
confidence: 87%
“…As hepatic fibrosis progresses, the liver parenchyma cell volume decreases and can cause changes in viral loads. Previous studies have reported that the severity of hepatic injury is not consistent with the serum HCV load in HCV-infected patients (12,13). Therefore, it can be hypothesized that hepatic injury is associated with the HCV load in the parenchyma cells of HCV-infected patients.…”
Section: Introductionmentioning
confidence: 87%
“…Morphometric analysis was also carried out to verify the percentage of coagulation necrosis for each treatment. Necrosis areas were measured as adapted from our previous reports [ 8 , 37 ], with a total of three sections (20 μm far) for each tumor collected from five mice per group.…”
Section: Methodsmentioning
confidence: 99%
“…The treatment control group was given PN at a daily dose of 1.5 g. Both drugs were well mixed into the ducks' feed; half the daily dose was given in the morning and half in the evening for 2 months. 6 serum anti-HCV was determined by enzyme-linked immunosorbent assay (ELISA), serum HBV DNA was determined by polymerase chain reaction (PCR) 7 and serum HCV RNA was detected by reverse transcriptase (RT)-PCR. 8 Liver enzymes, including alanine transferase and serum bilirubin, were determined using an autobiochemical analysis machine (AU400; Olympus, Tokyo, Japan).…”
Section: Animal Modelmentioning
confidence: 99%